1997
DOI: 10.1073/pnas.94.16.8854
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus reticularis neurons mediate diverse inhibitory effects in thalamus

Abstract: Detailed information regarding the contribution of individual ␥-aminobutyric acid (GABA)-containing inhibitory neurons to the overall synaptic activity of single postsynaptic cells is essential to our understanding of fundamental elements of synaptic integration and operation of neuronal circuits. For example, GABA-containing cells in the thalamic reticular nucleus (nRt) provide major inhibitory innervation of thalamic relay nuclei that is critical to thalamocortical rhythm generation. To investigate the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 44 publications
(44 reference statements)
7
123
0
Order By: Relevance
“…Both of these inputs to TRN are excitatory. In striking contrast, the projections from TRN back on the LGN are inhibitory (Cox et al, 1997;Kim et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Both of these inputs to TRN are excitatory. In striking contrast, the projections from TRN back on the LGN are inhibitory (Cox et al, 1997;Kim et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…0.03 mS, and increased to 0.2 mS under in vivo conditions. For an estimated quantal conductance of GABA A synapses of 300 pS (Cox et al 1997;Le Feuvre et al 1997;Ulrich & Huguenard 1997), the threshold conductances predict that between 100 (control) and 660 (in vivo) GABAergic synapses must be co-activated to elicit a rebound burst in thalamic relay cells. Morphological studies indicate that a single axon from reticular neurons establish, on average, 60 synapses on the same postsynaptic relay cell (Kim et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the amplitude of unitary nRT-to-nVPM IPSCs of older rats (P9 -P16) varied widely from 18 to 514 pA (Cox et al, 1997). However, there is no systematic study of the nRT-to-nVPM IPSCs during the first postnatal week; therefore, we studied the changes with age of the GABA A -mediated nRTto-nVPM IPSCs from P0 to P9 (Table 1, Fig.…”
Section: Postnatal Development Of the Thalamic Inhibitory Feedback Loopmentioning
confidence: 99%